Mosque as metaphor analogy: incorporating Islamic values in desktop design - Nasruddin, Zan Azma; Hussin, Husnayati (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper addresses culturally based factors within user interface design. There are challenges and dilemmas in recognizing values and ideals in culture on an interface design. As value added in the interface design related to culture, elements of culture values should play an important root so that users are encouraged to feel the beauty of meaning in the interface. Culture-Centred Design (CCD) is applied, thus a redesigned interface prototype, incorporating Islamic values for Muslim users in Malaysia as a target group is discussed. A culturally specific ‘mosque’ is developed to be desktop design and culture based religious icons are created within the design. The rationales of the design are described including several ayats from the Holy Quran are revealed as to support the important needs in the process of development the interface prototype for muslim users.